Institutional and macroeconomic stability mediate the effect of auctions on renewable energy capacity - Pablo Mac Clay; Jan Börner; Jorge Luis Sellare (University of Bonn, Center for Development Research (ZEF), 2022)
Decarbonizing the global energy matrix through investments in renewable energy (RE) is considered a pathway to mitigate the effects of global climate change. Auctions have become an increasingly popular policy instrument for this purpose. In the last few years, auctions have been rapidly adopted by low- and middle-income countries due to their flexibility and several theoretical advantages to mitigate risks deriving from poor business environments. Previous research has used data from higher-income countries and two-way fixed effects models to estimate the effects of auctions on RE capacity, mostly with favorable results. However, none of these studies accounted for heterogeneous treatment effects across units to explore whether auctions are effective in countries with unstable business environments. Here we analyze if auctions can foster RE in countries facing macroeconomic instability or poor institutional quality. For this purpose, we have drawn from multiple publicly available databases to build a panel dataset covering 98 countries for the period 2000-2020. Our definition of RE includes solar, wind, and biomass sources. We show results for each RE source separately and all of them combined. We first cluster countries in terms of the quality of their business environment and then perform a differences-in-differences analysis considering staggered treatment adoption. Our results show that auctions positively affect RE capacity, but average treatment effects are higher for countries with better business environments. Thus, caution is needed in adopting this instrument, especially in countries exposed to macroeconomic or institutional instability. At the same time, dynamic treatment effects suggest that the policy needs time to show results.
Keywords: L94; Q42; Q48; Q54; Q58; 330; renewable energy; auctions; policy evaluation; difference-in-differences; causal inference